Role of Oxidative Stress as Key Regulator of Muscle Wasting During Cachexia - Vilos-Ortiz, C (Hindawi Limited, 2018)
Skeletal muscle atrophy is a pathological condition mainly characterized by a loss of muscular mass and the contractile capacity of the skeletal muscle as a consequence of muscular weakness and decreased force generation. Cachexia is defined as a pathological condition secondary to illness characterized by the progressive loss of muscle mass with or without loss of fat mass and with concomitant diminution of muscle strength. The molecular mechanisms involved in cachexia include oxidative stress, protein synthesis/degradation imbalance, autophagy deregulation, increased myonuclear apoptosis, and mitochondrial dysfunction. Oxidative stress is one of the most common mechanisms of cachexia caused by different factors. It results in increased ROS levels, increased oxidation-dependent protein modification, and decreased antioxidant system functions. In this review, we will describe the importance of oxidative stress in skeletal muscles, its sources, and how it can regulate protein synthesis/degradation imbalance, autophagy deregulation, increased myonuclear apoptosis, and mitochondrial dysfunction involved in cachexia. Copyright © 2018 Johanna Ábrigo et al.